Robotic and Non-Robotic Control of Astrophysical Instruments - Gerd Küveler; Van Dung Dao; Axel Zuber; Renzo Ramelli (Advances in Astronomy)
We present a system of device control programs, developed for the solar observatory at Locarno/Switzerland (IRSOL). Because these programs are implemented as servers—clearly separated from the higher levels—scientific instruments, for example, telescopes, can be operated both in a user-controlled mode (GUI, telnet) and in a fully automated mode by use of a script. Astronomical instruments such as telescopes or spectrographs will be responded to by ASCII command strings, which are the same for all clients. In case a device control software does not support multiclient operation or in case it is used together with other devices in a complex measuring procedure, it is worthwhile implementing an intermediate layer that relieves the individual device control servers of routine tasks and provides for a safer operational sequence. In addition, the system may make use of an easy-to-learn script language specialised for controlling fully automated processes.